2020
DOI: 10.3390/en13205340
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Blasting Energy Distribution and Utilization Efficiency Using Water Jet Test

Abstract: The blasting stress wave and blasting gas generated by explosive blasting are the two main motive powers of rock fragmentation. An experimental method based on water jet test is used to study the energy distribution ratio of blasting stress wave and blasting gas; the utilization efficiency of blasting energy under different borehole constraint conditions is also analyzed. It proves that the blasting stress wave does not cause the water jet, and the blasting gas is the only power of the water column jet. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The reflected wave propagating inside and the subsequent blasting gas work together to continuously expand and compress the original media in the blasthole. In this process, the explosive gas continues to expand, the volume increases, and the pressure decreases; the initial air is compressed, the volume decreases, and the pressure rises (Ding et al, 2020). At the time when the pressure of the explosion gas reduced by the expansion is equal to the pressure of the original air in the blast hole, an equilibrium state is reached at this time, the expansion and compression process ends, and a quasi-static pressure is formed in the blast hole.…”
Section: Quasi-static Pressure Promotes Crack Propagationmentioning
confidence: 99%
“…The reflected wave propagating inside and the subsequent blasting gas work together to continuously expand and compress the original media in the blasthole. In this process, the explosive gas continues to expand, the volume increases, and the pressure decreases; the initial air is compressed, the volume decreases, and the pressure rises (Ding et al, 2020). At the time when the pressure of the explosion gas reduced by the expansion is equal to the pressure of the original air in the blast hole, an equilibrium state is reached at this time, the expansion and compression process ends, and a quasi-static pressure is formed in the blast hole.…”
Section: Quasi-static Pressure Promotes Crack Propagationmentioning
confidence: 99%
“…Through the water jet test, Ding C.X. et al [12] found that the energy of the blasting gas and the blasting stress wave accounted for about 64% and 36% of the total energy produced by the explosion. Goto A. et al [13] simulated volcanic explosions through field explosion experiments.…”
Section: Introductionmentioning
confidence: 99%
“…e Brazilian and international admissibility standards of blasting-induced vibration, the minimum distance between the mine and the community, and the constants obtained from the regression were used to establish the maximum explosive charge per delay for an acceptable ground vibration level that would not cause structural damage and human discomfort [20]. For the cylindrical charge, many scholars combined dynamic caustics, super dynamic strain testing, and numerical analysis methods to study the explosion stress and strain field of the cylindrical charge and the evolution law of the local stress field at the tip of the explosion crack [21][22][23][24]. Some scholars have also conducted intensive research on the different charge structures of columnar drug packs.…”
Section: Introductionmentioning
confidence: 99%